Sustainable development of coal-based circular economy park: a case study - Wei Zhen; Chang Zhenxing; Chen Chong (E3S Web of Conferences, 2020)
China is one of the world’s largest producing and consuming countries of coal. In decades, the coal-based resource type cities of China are facing economic reduction and environment degradation, because of the rapid resource exhaustion and single industrial structure. However, as a policy instrument for sustainable development, a nationwide circular economy model has been implemented at the strategic plan of new coal mines to succeed in the future dilemmas of economic depression, energy shortage, and environmental pollution. Generally, most of the coal resources are buried in the underdeveloped north-western areas with a more vulnerable eco-environment, which means a great distance between the energy supply source and the demand markets as well. Therefore, through comparing and analysing several successful coal-based circular industry chains, and discussion and evaluation of a new model of the circular economy park (CEP), this paper aims to enhance the understanding of coal mine sustainable development and shed light on the relationship between resource exploitation and local economic development.